Asian Entrepreneurship - Dana, Leo Paul (London ; Sage Publications, 2015)
It is widely accepted that entrepreneurship contributes to development, imparting a positive effect on society; creating employment, economic expansion, a larger tax base, and more consumer well-being. This is increasingly supported by research, and acknowledged by governments across Asia and around the world. Bringing together some of the most significant research to come out of the field in the past few decades, this major work presents a nuanced reading of key concepts of Asian entrepreneurship, in depth, and with emphasis on comprehensive, scholarly discussion. Entrepreneurship differs greatly across Asia: cultural values, government policy and a variety of other factors, including a nation's colonial experience, all affect the way entrepreneurship is understood and studied. This collection is designed to clarify and enable clearer understanding of the various cultural and historical factors which have shaped the field of entrepreneurship in Asia.
v.1. Contextual issues -- v.2. Human capital -- v.3. External support -- v.4. Internaionalisation -- v.5. Niche articles.
Keywords: Entrepreneurship -- Asia -- Handbooks, manuals, etc; Asia -- Economic conditions